Psychological Analysis of Executive Body Manager’s Competence Factor Structure - Malimon, Liudmyla (Psychological Prospects Journal, 2015)
The article is devoted to competence approach to managerial activity of state jurisdiction research. It was mentioned that level of government officials competence in many ways defines the level of faith of population to authoritative institutions and state in the whole. It was shown that state management from the point of view of socio-psychological approach is a kind of social management within which demands to managerial competence of government officials are revealed.It  was  analyzed  the  notions  of  “competence”   and   “expert   knowledge” their content and peculiarities of interpretation  in  scientific  sources  were  defined. The generalized definition of managerial competence as integral personal formation which is manifested on the level of chief’s personality (structural-personal component), style of his managerial activity (action-functional component) and interaction within the systems “chief-staff”, “chief-subordinate” taking into account specific organizational  situation (interactive-situational component) was offered. It  was analyzed the results of  factor  analysis  of  empiric  data  which  were  obtained  as a result of studying of structural components of managerial competence of local executive authority chiefs. It was interpreted the distinguished factors of managerial competence: strict understanding of functional-official obligations; socio- psychological qualities and communicative potential of a chief;  orientation  at securing of psychological comfort in staff; innovation and democratism  of managerial activity; chief’s prestige and skill of power usage; self-statement in managerial activity; organizational-research position in staff; authoritarian monocratic style of management. It was shown that the biggest factorial load falls at two main components: action-functional and structural-personal; the shortest percentage of variance characterizes disposition of a chief to authoritarian monocratic style of management.
Keywords: competence, expert knowledge, competence approach, chief managerial competence, governmental service, factor structure of managerial competence of a chief